Performance based self-esteem and athlete-identity in athlete burnout: A person-centered approach - Gustafsson, H.; Martinent, G.; Isoard-Gautheur, S.; Hassmén, P.; Guillet-Descas, E. (Psychology of Sport and Exercise, 2018)
Performance-based self-esteem and a self-identity dominated by being an athlete have been associated with athlete burnout. Our aim is to extend previous research by adopting a person-centered approach and examining whether profiles of burnout can be identified based on the athletes` identity and performance-based self-esteem. Swedish junior athletes completed measures of athlete burnout, athlete identity, and performance-based self-esteem. Latent profile analysis identified four groups: Low burnout profile (n = 131), Moderate burnout profile (n = 178), Moderately high burnout profile (n = 125) and High burnout profile (n = 37). Higher scores of athletic identity were significantly less likely to be in the high burnout profile and athletes with higher scores of performance-based self-esteem were significantly more likely to be in the high burnout profile compared to the other three burnout profiles. These findings suggest that athletes with a performance-based self-esteem might be at greater risk of experiencing burnout.